PERBANDINGAN BERBAGAI VARIETAS UBI JALAR DITINJAU DARI PENDAPATAN USAHATANI DAN PEMASARAN DI KABUPATEN MALANG COMPARISON AMONG VARIOUS SWEET POTATO VARIETIES FOCUSED FROM FARM INCOME AND MARKETING AT MALANG REGENCY - Ariadi, Bambang Yudi (Pembangunan Pedesaan, 2006)
The research purposed to identify varieties of sweet potato cultivated in Malang Regency and its comparison focused from farm and marketing. The population observed were farmers and marketing institution of sweet potato obtained from three districts, i.e., Pakis, Ngajum, and Nongkojajar. The farmerâs samples were determined by disproportionate stratified random sampling based on stratum of sweet potato. Each variety was presented by 20 farmers as sample. Sampling technique for marketing institution was snowball sampling. The data was analyzed descriptively by mathematics analysis for counting farm and marketer profit. The research result showed that there were six varieties of sweet potato cultivated and gave prospective in Malang Regency, i.e., Steven, Mr. Ong, IR Melati, Sari, Ubi ungu, and Gunung Kawi. The average farm income per_hectar at each variety was Steven Rp10,322,636.00; Sari Rp8,802,000.00; Mr.Ong Rp7,075,000.00; Ubi Ungu Rp5,905,936.00; IR Melati Rp4,309,167.00, and Gunung Kawi Rp3,976,500.00. Rural people at the research place prefer cultivated sweet potato compared to rice or other commodities because of the profit comparison. In term of marketing activity, the highest marketer profit was found at the variety of Ubi Ungu and Gunung Kawi, because the product price was more expensive so that the price margin was also bigger.